ХУДОЖНЯ ІНТЕРПРЕТ АЦІЯ ТВОРІ В МИСТЕЦТ В В ТЕ ОРІЇ ТА ПР АКТИЦІ НАУКОВОГО АНАЛІ ЗУ - Lysenko, O (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the accepted types of interpretation (technical, verbal,scientific and accepted), that refer to the interpretation of literary and art works of different kinds of art. The essence of the notion “interpretation of the works of art” reveals in the sphere of scientific investigation